DFOS measurements for strain analysis of anchorage zone in 57‐year‐old posttensioned precast girder using static and high‐frequency approach. (15th July 2021) - Derkowski, Wit; Sieńko, Rafał; Walczak, Rafał; Howiacki, Tomasz; Bednarski, Łukasz
Abstract: The aging engineering infrastructure is a growing problem in many countries and thus a challenge to make optimal decisions for their further safe operation. Therefore, effective diagnostic solutions are being sought to enable a reliable assessment of their technical condition. The article presents the results of static and high‐frequency strain measurements of a 57‐year‐old posttensioned crane girder, dismantled from one of the production halls. In particular, the anchorage zone and transmission length of the tendon related to the quality of cement injection around the prestressing tendon were analyzed. For this purpose, a distributed fiber optic sensing (DFOS) technique was applied, which allows performing strain measurements with a spatial resolution starting from 2.6 mm (almost 385 measuring points per 1 m of the optical fiber). The application of such an approach allowed for detailed analysis in both longitudinal and transverse directions, including crack detection and estimation of their widths. The article describes in detail the sensing fibers and applied methodology, as well as the results of both static and high‐frequency tests performed under laboratory conditions during cutting one of the tendon's anchorage off.